"The Dating Game:" Using Speed Dating in the College Classroom. Issue 3 (2nd July 2020) - Jones, Megan M.; Ritter, Lacey J.
Abstract: This article describes and evaluates an in-class activity and discussion called "The Dating Game, " which resembles the speed-dating process in modern, love-based societies. Activity effectiveness was analyzed through post-activity responses from students at three schools (N = 126) and course evaluations (N = 54). Data suggest this activity helps students understand dating-themed lecture material, as well as more abstract concepts like social interaction and impression management. Additional benefits include: (1) an opportunity for students to become acquainted toward the beginning of a semester; and (2) increased levels of awareness of classmates' social locations, leading to better conversation and interpersonal activities.